PDF Manajemen Pembelajaran PAI di Sekolah Dasar Negeri Bojong - Ahyun Rofiah; Farid Setiawan; Ema Fidiatun Khasanah; Yusril Muhamad Anjar; Elitawati (Jurnal Tinta: Jurnal Ilmu Keguruan dan Pendidikan, 2022)
The purpose of this research is to find out 1). understanding of learning management, 2) the stages of learning management, 3) how to plan and develop the learning management. The subject we studied was at the Bojong State Elementary School. In this study we used qualitative methods and data collection. The technique used is observation, interviews, and data collection. After all the data is collected, it is analyzed with data from library analysis and then described so that it will be easier to understand and clear. The results of the research conducted at the Bojong State Elementary School include: 1) learning management is a learning planning process through various stages so that it can achieve the desired goals. 2) the stages carried out in learning management include planning, implementation, and evaluation, as well as follow-up to the evaluation. 3) the development carried out in learning management is by paying attention to the background of the students, the facilities and infrastructure available at the school, the availability of tutors/teachers/teaching staff, the number of effective days, the distribution of additional activities other than classroom learning, as well as the development carried out by residents. schools, starting from the principal and educators. But the most important thing in carrying out learning management is the teacher as the implementer in the teaching and learning process in the classroom, then the principal, and the supervisor as the learning supervisor.